The Dynamic Relationship Between Energy Consumption, Foreign Direct Investment, Urbanization, and Carbon Emissions - Dayu Ratih Yogiswari; Aminudin Ma'ruf (Jurnal Ilmu Ekonomi Terapan, 2026)
Objective: This empirical study examines the relationship between energy consumption, foreign direct investment (FDI), and urbanization on carbon emissions. It is relevant to sustainable development, particularly concerning the dynamics of energy, capital flows, and urbanization trends within an environmental context. Design/Methods/Approach: A quantitative approach was employed, utilizing time series data from 1990 to 2022. Analysis was conducted using the Autoregressive Distributed Lag (ARDL) Bounds Test model to estimate both short-term and long-term relationships between the variables. Findings: Energy consumption significantly increases carbon emissions; a one-unit rise in energy consumption is associated with a 981,495-unit increase in emissions in the long term. Similarly, FDI also raises emissions in the long term, whereas urbanization reduces them. These results underscore the significant influence of fossil-fuel energy use and highlight the importance of green investment and sustainable urban development. Originality/Value: The main contribution of this study lies in its use of the latest data and the ARDL approach to distinguish between short-term and long-term effects. This study enriches the environmental economics literature in developing countries by focusing on the roles of energy, foreign capital, and urbanization. Practical and policy implications: The study's results offer practical guidance for sustainable development policies. The government should encourage the use of environmentally friendly energy, foreign direct investment towards green technology, and leverage urbanization to foster sustainable cities. These findings can serve as a reference for formulating future regulations and strategies to reduce carbon emissions.